Respuesta :
Answer:
6
Step-by-step explanation:
x = 2 y = 6 Explanation: y = 3 x (1) y = x + 4 (2) Subtracting (1) - (2): 0 = 2 x − 4 2 x = 4 x = 4 2 = 2 y = 3 × 2 = 6
Answer:
x = 2.5
y = 6.5
Step-by-step explanation:
You can solve this by setting the two equations equal to each other, like so:
x + 4 = 3x - 1
Subtract x from both sides:
x + 4 = 3x - 1
-x - x
__________
4 = 2x - 1
Add 1 to both sides:
4 = 2x - 1
+1 + 1
_________
5 = 2x
Divide by 2:
2.5 = x
Plug in 2.5 for x into the equation:
y = x + 4
y = 2.5 + 4
y = 6.5